Correlation Study Between Habit in Watching English Movies and Vocabulary Mastery in English Education Department Perjuangan University - Dede Meti Agustin Suryani; Tasya Nurfajriah; Khoerunisa; Putri Leonita Hermawan; Elih Haedaroh Muharomah (Journal of Applied Linguistics (ALTICS), 2024)
The purpose of this study is to determine whether or whether there is a link between students' routine of viewing English movies and their level of vocabulary mastery, as well as the degree to which there is a correlation between the two factors. The correlational study research design was used for the present investigation. It indicates that the researcher does not provide the pupils with any therapy of any kind. There is no explanation provided prior to this. The exam is only administered to the pupils by the researcher. The researcher obtained the sample by a method known as cluster random sampling. As a result of using the sampling approach, the researcher selected students who were in their sixth semester of the English education study program to act as the sample. It has been determined via the use of the correlation product moment in the study calculation that the observed r value is 0.798, whereas the table r value is 0.320 in significant 5% and 0.413 in significant 1%. The number 61 represents the average number of minutes per week that students spend viewing English movies. The standard score for the knowledge of vocabulary is 60.12 points. It demonstrates that the observed r value is greater than the r value in the table. What it indicates is that Ho is acceptable whereas Ha is not accepted. The inference that can be drawn from these findings is that there is a significant positive link between the students' routine of viewing English movies and their level of vocabulary knowledge. Keywords: habit, English, Students, Vocabulary Mastery.